Pendampingan Panen Tanaman Kenaf Pada Budidaya Tanaman Kenaf Di Desa Suradadi Kabupaten Tegal - Niken Wahyu Cahyaningtyas; Sri Murdiati; Yuni Utami; Yuniarti Herwinarni; Faiz Irsyad Prasetyo; Muhammad Siddik Erdi Wicaksono; Baihaqi Fanani; Sari Wiyanti (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
Most people in Suradadi Village have a low level of education, especially the farmers. This can be seen from the cropping pattern of agricultural land that has been passed down from generation to generation only to plant rice and corn, then the land is left abandoned after entering the dry season. The mentoring activity aims to assist in optimizing dry land utilized for kenaf plants as an alternative crop. This community service activity program is not only on planting kenaf seeds but also assisting maintenance until harvest. The method of this activity goes through several stages, namely determining the theme, literature study, briefing, implementing activities and preparing the final report. Because kenaf plants are still unfamiliar and not yet known by farmers, in the implementation of this assistance activity, after the seedling period is in the plant maintenance period by checking the suitability of the age of 100 days with the growth of kenaf plants and checking the growth of flowers and the release of kenaf plant fruit at the age of 120-150 days. Briefing activities regarding the equipment needed and harvesting procedures. The equipment needed is only machetes and sickles to cut plant stems and immediately separate the stems, leaves and fruit of kenaf plants.